מה ((x ^ 2-16) / (x ^ 2-6x + 8)) * (5x-10) / (3x 12))?

מה ((x ^ 2-16) / (x ^ 2-6x + 8)) * (5x-10) / (3x 12))?
Anonim

תשובה:

#5/3#

הסבר:

אתה יכול גורם, אם זה אפשרי, ולאחר מכן לפשט:

מאז

# a ^ 2-b ^ 2 = (a-b) (a + b) #

אתה יכול גורם

# x ^ 2-16 = (x-4) (x + 4) #.

מאז # x ^ 2 + (a + b) x + ab = (x + a) (x + b) #

אתה יכול גורם

# x ^ 2-6x + 8 = (x-4) (x-2) #.

מאז

# ax + ab = a (x + b) #

אתה יכול גורם

# 5x-10 = 5 (x-2) # ו

# 3x + 12 = 3 (x + 4) #

אז יש לך

# (x ^ 2-16) / (x ^ 2-6x + 8) * (5x-10) / (3x 12) = #

# () (ביטול ((x-4)) ביטול ((x-4) (5 + 3)) 5/3 (3) (3 x 3)